Tanggung Jawab Notaris Atas Akta Perjanjian Pengikatan Jual Beli Saham Yang Dibalut Dengan Hutang Piutang - Edison Hatoguan Manurung; Sri Hartanto (Journal of Innovation Research and Knowledge, 2026)
Civil engineering practice requires professionals who possess not only strong technical competence but also high integrity and professional ethics in carrying out their duties and responsibilities. These three aspects are essential for ensuring the quality of construction work, public safety, and the successful implementation of infrastructure projects. This study aims to analyze the relationship between competence, integrity, and professional ethics in civil engineering practice. The study employed a descriptive-analytical approach by reviewing relevant scientific literature on professional competence, integrity, and professional ethics in civil engineering and related engineering professions. The data were analyzed through the processes of identification, classification, and synthesis of previous research findings concerning these three variables. The results indicate that competence plays a significant role in improving the quality of technical decision-making, work effectiveness, and compliance with professional standards. Integrity contributes to maintaining honesty, responsibility, transparency, and accountability in civil engineering practice. Furthermore, competence and integrity complement each other in shaping professional ethics. Competence provides the technical capabilities required to perform engineering tasks, while integrity ensures that these capabilities are applied responsibly in accordance with moral principles and professional codes of ethics. Therefore, continuous development of professional competence and the strengthening of integrity are essential to promote ethical, professional, and socially responsible civil engineering practice while ensuring public safety